2022
DOI: 10.3389/feduc.2022.780331
|View full text |Cite
|
Sign up to set email alerts
|

“Now I’m Not Afraid”: The Influence of Identity-Focused STEM Professional Organizations on the Persistence of Sexual and Gender Minority Undergraduates in STEM

Abstract: In comparison to work on women and historically excluded racial/ethnic minority students in science, technology, engineering, and math (STEM), research on sexual and gender minority (SGM) students in STEM is somewhat incipient. There is little scholarship available on SGM-focused STEM organizations (e.g., oSTEM). Building on the previous literature, we examine how SGM-focused STEM organizations provide social capital, both expressive (e.g., emotional support) and instrumental (e.g., academic resources), that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…In addition, more research is needed to examine the longitudinal effects of K-12 STEM programming, including those offered in middle and elementary school, to determine impact on broadening STEM participation. Finally, work like ours, considering binary gender and race/ethnicity, can be augmented by added intersectional lenses attending to the impact of additional identities, such as sexual and Wao et al International Journal of STEM Education (2023) 10:25 gender minority identities (e.g., LGBTQIA+; Campbell-Montalvo et al, 2022a, 2022d. These areas are ripe for investigation by researchers.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, more research is needed to examine the longitudinal effects of K-12 STEM programming, including those offered in middle and elementary school, to determine impact on broadening STEM participation. Finally, work like ours, considering binary gender and race/ethnicity, can be augmented by added intersectional lenses attending to the impact of additional identities, such as sexual and Wao et al International Journal of STEM Education (2023) 10:25 gender minority identities (e.g., LGBTQIA+; Campbell-Montalvo et al, 2022a, 2022d. These areas are ripe for investigation by researchers.…”
Section: Discussionmentioning
confidence: 98%
“…In this section, we explore the possible barriers HUG students face when pursuing STEM degrees along the career research roadmaps. While studies have shown that non-binary and transgender people have similar experiences as cisgender women, they face augmented difficulties (Blackburn, 2017;Conrad et al, 2021;Miles and Naumann, 2021;Campbell-Montalvo et al, 2022a). Challenges and compounding difficulties will both be addressed in this section.…”
Section: Obstacles and Possible Solutionsmentioning
confidence: 96%
“…However, research shows that LGBTQ+ populations face significant health disparities and discrimination (Gonzales et al, 2016;Kronk et al, 2022;Samuels et al, 2021). Not only are LGBTQ+ individuals underrepresented in STEM (Cech and Waidzunas, 2021), but they are more likely to be harassed as well as face stigma, discrimination, and bias (Campbell-Montalvo et al, 2022a;Cech and Waidzunas, 2021;Freeman, 2018;Freeman, 2020;Hughes, 2018;Marr et al,2022;Palmer et al, 2022). The distinct barriers that LGBTQ+ trainees face because of their sexual orientation and/or gender identity impede their career advancement despite making considerable contributions to STEM fields (Cech and Waidzunas, 2021;Marr et al, 2022).…”
Section: Sexual Orientation Identitymentioning
confidence: 99%